2001
DOI: 10.1002/zoo.1019
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of excretion of fecal estradiol and progesterone and urinary chorionic gonadotropin in Grevy’s zebras (Equus grevyi): Ovulatory cycles and pregnancy

Abstract: The ovulatory cycle and pregnancy of the endangered Grevy's zebra (Equus grevyi) was characterized by analyzing excretion patterns of fecal estradiol and progesterone. Pregnancy was further described by assay of urinary equine chorionic gonadotropin. Courtship and mating behavior were similar to that seen in the domestic horse, but cycle length was longer, ranging from 28 to 35 days. Steroid hormone profiles during pregnancy were likewise similar to the horse, but gestation length was longer (391 and 406 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
5
20
0
1
Order By: Relevance
“…It has been reported that measuring fecal progestagens can be used for monitoring the estrous cycle in the domestic horse [15][16][17], Przewalski's horse [10] and Grevy's zebra [11]. In our study, the change in fecal progestagens showed ovarian cyclicity and was an average of 22.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that measuring fecal progestagens can be used for monitoring the estrous cycle in the domestic horse [15][16][17], Przewalski's horse [10] and Grevy's zebra [11]. In our study, the change in fecal progestagens showed ovarian cyclicity and was an average of 22.…”
Section: Discussionsupporting
confidence: 53%
“…Fecal progestagen analyses are used to assess luteal activity in many Perissodactyla species, such as the domestic horse (Schwarzenberger et al 1996a;Palme et al 2001), the zebra (Asa et al 2001) and several rhinoceros species (Schwarzenberger et al 1996b(Schwarzenberger et al , 2000Berkeley et al 1997;Heistermann et al 1998;Patton et al 1999;Brown et al 2001) and would be invaluable for tapirs. However, evaluations thus far have failed to yield data that are biologically relevant, or correlate with serum profiles (A. Rubiano et al, unpubl.…”
Section: Feasibility Of Noninvasive Hormone Monitoringmentioning
confidence: 99%
“…There are seven extant species in the Equidae family [1] and only a few published reproductive studies, including those for the Grévy's zebra (Equus grevyi) [2], mountain zebra (Equus zebra) [3,4], plains zebra (Equus burchellii) [5,6], and Przewalski's horse (Equus ferus przewalski) [7][8][9]. The reproductive physiology of wild asses (three species; eight subspecies [10]) has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%